DETERMINATS OF PATIENT SATISFACTION IN MEDICINE COLLECTION SERVICES AT PHARMACEUTICAL INSTALLATION BANDA RAYA HEALTH CENTER IN BANDA ACEH - Putra Utama, Anugerah Akbar; arbi, anwar; Lina, Intan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: The Banda Raya Health Center (Puskesmas), reports that the number of patients who purchase medicines from the pharmacy at the Community Health Center Installation is decreasing every year, this is thought to be because the medicines needed are not available at the pharmacy. Patients who do not want to queues for a long time and prefer to buy medicines from the outside of the health center. Convenience and poor service procedures are also the reasons why patients feel dissatisfied with medication collection services. This study aims to determine patient satisfaction in medicine collection services at the the Banda Raya Community Health Center Pharmacy Installation, Banda Aceh City. Method: Quantitative research with cross sectional design. The sample in this study were patients/families of patients who purchase medication at the Banda Raya Health Center Pharmacy Installation, totaling 49 patients from January to March 2020, using the Accidental Sampling technique. This research was conducted on August 3-11, 2020. Bivariate analysis used SPSS with the chi square statistical test. Results: Univariate analysis showed that 69.4% of patients were dissatisfied, 75.5% were uncomfortable, 67.3% had a negative attitude, 73.5% had poor human relations, 75.5% had poor service procedures, and 77.5 % no drug availability. The results of the bivariate analysis showed that there was a relationship between comfort (P value = 0.004), attitude (P value = 0.002), human relations (P value = 0.001), service procedures (P value = 0.001), and drug availability (P value = 0.021 ) with patient satisfaction in drug collection services at the Pharmacy Installation of the Banda Raya Health Center, Banda Aceh City. Conclusion: Puskesmas are expected to be able to provide sufficient medicine and provide training for pharmaceutical service staff regarding good health service training such as carrying out the ‘3 S’ (Greet, Smile, Care) so that patients feel satisfied and comfortable.